The bitter taste receptor T2R38 is an independent risk factor for chronic rhinosinusitis requiring sinus surgery. Issue 1 (2nd December 2013) - Adappa, Nithin D.; Zhang, Zi; Palmer, James N.; Kennedy, David W.; Doghramji, Laurel; Lysenko, Anna; Reed, Danielle R.; Scott, Thomas; Zhao, Nina W.; Owens, David; Lee, Robert J.; Cohen, Noam A.
<x xml:space="preserve">Abstract</x> Background The bitter taste receptor T2R38 was recently described to play a role in upper airway innate mucosal defense. When activated by bacterial quorum‐sensing molecules, T2R38 stimulates the ciliated epithelial cells to produce nitric oxide (NO), resulting in bactericidal activity and an increase in mucociliary clearance (MCC). Polymorphisms within the T2R38 gene (TAS2R38) confer variability in activation of the receptor yielding dramatic differences in upper airway defensive responses (NO production and accelerated MCC) to microbial stimulation based on genotype. Our objective was to determine whether the nonprotective TAS2R38 polymorphisms, which render the receptor inactive, correlate with medically recalcitrant chronic rhinosinusitis (CRS) necessitating surgical intervention in the context of known risk factors, and thus identify whether the TAS2R38 genotype is an independent risk factor for patients undergoing functional endoscopic sinus surgery (FESS). Methods CRS patients undergoing primary FESS were prospectively genotyped for TAS2R38. Chi‐square analysis was performed on the genotype distribution with respect to other risk factors, including allergies, asthma, nasal polyposis, aspirin sensitivity, diabetes, and smoking exposure. Results Seventy primary FESS patients were genotyped demonstrating a statistically significant skewing from the expected distribution of the general population (p < 0.0383). CRS patients with a particular polymorphism seemed less likely to have allergies, asthma, nasal polyposis, aspirin sensitivity, and diabetes, but this did not demonstrate statistical significance. Conclusion Our investigation suggests that TAS2R38 genotype is an independent risk factor for patients failing medical therapy, necessitating surgical intervention.